Screening of mangrove - derived bacteria from Ninh Ich, Ninh Hoa, Khanh Hoa for antimicrobial producers - Mien, Pham Thi; Khoa, Nguyen Van (Vietnam Journal of Marine Science and Technology, 2020)
In the context of global climate changes, mangroves are not only considered as an important ecological region but also as a source of exploitation of specific biological objects for researches and applications. In this study, mangrove-derived bacteria were isolated and screened for antimicrobial producers. Also, the strains with potential antibacterial activity were identified by 16S rRNA gene analysis. Results showed that 43% of 21 strains possessed antibacterial activity. The strain R10 showed inhibition against all four indicator bacteria and was identified as Bacillus pumilus with the highest sequence similarity of 100% to Bacillus pumilus NCTC10337 (GenBank accession number LT906438.1). The strain R7 inhibited Serratia marcescens causing severe “white spot” disease in reef building coral Acropora palmata and was closely related to Bacillus toyonesis BCT 7112 (GenBank accession number NR121761.1) with 99% sequence similarity. The strain R3 was the strongest strain against Bacillus subtilis compared with other strains which revealed the same antimicrobial activity pattern. The strain R3 was affiliated with Bacillus marisflavi TF-11 (GenBank accession number NR025240.1) with 98% sequence similarity and may be considered to represent new species. Moreover, the strain R9 inhibited only Gram negative tested strain and this strain was considered as a potential candidate for further search of antibiotics with spectrum of Gram negative bacteria.